Influence of the near-surface regions of the space charge in semiconductor crystals on defect transformation stimulated by the action of magnetic fields - Milenin, G.V.; Redko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The mechanisms of electromagnetic radiation in the near-surface regions of semiconductors depleted of the majority charge carriers under the action of magnetic fields, the induction vector of which is parallel to the surface of the crystal, have been analyzed. The relationships for estimating the radiation power of space charge regions have been derived. Проаналізовано механізми електромагнітного випромінювання у приповерхневих областях напівпровідників, збіднених основними носіями заряду під дією магнітних полів, вектор індукції яких паралельний поверхні кристала. Отримано співвідношення для оцінки потужності випромінювання областей просторового заряду.